2020
DOI: 10.1016/j.ijscr.2020.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Jejunojejunal intussusception following jejunostomy closure: A case report

Abstract: Highlights Ileocolic intussusception is the most common type of intussusception. Jejunojejunal intussusception rarely occur. Most common Causes of intussusception in adult are adhesion, adenoma, lipoma. Jejunojejunal intussusception may be a complication of a jejunostomy feeding tube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Carucci et al reported a series of four cases of jejunojejunal intussusception following a jejunostomy feeding tube with distinguishable radiographic findings while the feeding tube was still in place [ 8 ]. However, radiography has its diagnostic limitations as Kareem et al reported a case of adult jejunojejunal intussusception secondary to GJ placement with no distinguishable findings on CT [ 9 ]. The findings in our patient's CT clearly demonstrated a telescope phenomenon surrounding the jejunostomy limb and were amenable to endoscopic reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Carucci et al reported a series of four cases of jejunojejunal intussusception following a jejunostomy feeding tube with distinguishable radiographic findings while the feeding tube was still in place [ 8 ]. However, radiography has its diagnostic limitations as Kareem et al reported a case of adult jejunojejunal intussusception secondary to GJ placement with no distinguishable findings on CT [ 9 ]. The findings in our patient's CT clearly demonstrated a telescope phenomenon surrounding the jejunostomy limb and were amenable to endoscopic reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Adults who have intestinal intussusception on a jejunostomy tube experience this extremely uncommon complication very infrequently. It symbolizes a surgical emergency that calls for prompt diagnosis and treatment, which is frequently surgical, as we demonstrate in this instance 2 . In order to provide nutrition to individuals who are unable to take it orally owing to illnesses affecting the stomach, esophagus, pancreas, duodenum, liver, or biliary system, a tube is put in the lumen of the proximal jejunum 3 .…”
Section: Introductionmentioning
confidence: 99%
“…It symbolizes a surgical emergency that calls for prompt diagnosis and treatment, which is frequently surgical, as we demonstrate in this instance. 2 In order to provide nutrition to individuals who are unable to take it orally owing to illnesses affecting the stomach, esophagus, pancreas, duodenum, liver, or biliary system, a tube is put in the lumen of the proximal jejunum. 3 Mechanical, bacterial, gastrointestinal, or metabolic problems have been reported with jejunostomies.…”
Section: Introductionmentioning
confidence: 99%